The use of potymerisable surfactants in emulsión copolymerization for coatings applications - Amalvy, Javier Ignacio (1998)
In this paper results obtained in high solids contení emulsión copolymerizations using polymerizable surfactcmts (surfmers) have been reviewed On the basis of the interpretation of the behavior of the surfmers (the conversión vs. time and their performance in stability tests and film properties), an optimal surfmer behavior has been defined, which means that all the added surfmer groups end up on the particle surface rather than being buried, which leads to inferior látex stability. One of the strategies that have been proposed to achieve this has been applied to prepare a well-defined styrene-butyl acrylate látex of which film can be easily be casi. Its properties in terms of mechanical stability, film water absorption, and film surfactant exhudation have been assessed and compared with these of a similar látex with sodiicm dodecyl sulfate. Other comonomer Systems have been studied as well with the maleic surfmer. In these Systems the surfmer behavior was less “optimum ”. For these lotices both mechanical stability and water absorption was assessed